KESENIAN RINDING GUMBENG PADA TAHUN 1970-1990 DI DESA BEJI, KABUPATEN GUNUNG KIDUL - Brigitha, Regina Natasha (Program Studi Pendidikan Musik, 2021)
Rinding is a musical instrument made of bamboo. This musical instrument comes from Beji Village, Gunung Kidul. Over time, this musical instrument has changed into the Art of Rinding Gumbeng. The purpose of this research is to provide new knowledge about the development of the art of Rinding Gumbeng for educators as well as to add written sources about local history that have minimal written sources. The method used in this research is a qualitative method with an ethnographic approach, with data collection techniques including interviews, literature study and documentation. This research was conducted in Beji Village, Gunung Kidul, Yogyakarta and the research was continued with literature study. The results shows that Rinding Gumbeng is an original art of the people of Gunung Kidul which is believed to have become an integral part of the farming system of the community. Initially, Rinding was a solo instrument that had a function as a means of ritual and has now developed into an ensemble that functions as a means of entertainment.